Revisiting the supplier selection problem: An integrated approach for group decision support - Kar, Arpan Kumar (Expert systems with applications, 2014)
•An integrated approach for group decision making in supplier selection is proposed.•Fuzzy AHP for group decision making was used to estimate group preferences.•Fuzzy Goal Programming for Discriminant Analysis was used subsequently.•Approach was tested and compared through a case study. Decision support for supplier selection is a highly researched theme in procurement management literature. However applications of group decision support theories are yet to be explored extensively in this domain. This study proposes an approach for group decision support for the supplier selection problem by integrating fuzzy Analytic Hierarchy Process (AHP) for group decision making and fuzzy goal programming for discriminant analysis. In the first step, the fuzzy AHP theory with the Geometric Mean Method has been used to prioritize and aggregate the preferences of a group of decision makers. Then consensus has been developed between these aggregated priorities using the Ordinal Consensus Improvement Approach. Subsequently, the consensual priorities of this group of decision makers have been integrated with fuzzy goal programming theory for discriminant analysis to provide predictive decision support. Finally it has been shown through a case study how the integrated approach using fuzzy AHP for group decision making and fuzzy goal programming with soft constraints has been more effective as compared to an existing approach for group decision making using only AHP.